Assessing community resilience: A CART survey application in an impoverished urban community. Issue 2 (2nd April 2016) - Pfefferbaum, Rose L.; Pfefferbaum, Betty; Zhao, Yan D.; Van Horn, Richard L.; McCarter, Grady S. "Mack"; Leonard, Michael B.
ABSTRACT: This article describes an application of the Communities Advancing Resilience Toolkit (CART) Assessment Survey which has been recognized as an important community tool to assist communities in their resilience-building efforts. Developed to assist communities in assessing their resilience to disasters and other adversities, the CART survey can be used to obtain baseline information about a community, to identify relative community strengths and challenges, and to re-examine a community after a disaster or post intervention. This article, which describes an application of the survey in a community of 5 poverty neighborhoods, illustrates the use of the instrument, explicates aspects of community resilience, and provides possible explanations for the results. The paper also demonstrates how a community agency that serves many of the functions of a broker organization can enhance community resilience. Survey results suggest various dimensions of community resilience (as represented by core CART community resilience items and CART domains) and potential predictors. Correlates included homeownership, engagement with local entities/activities, prior experience with a personal emergency or crisis while living in the neighborhood, and involvement with a community organization that focuses on building safe and caring communities through personal relationships. In addition to influencing residents' perceptions of their community, it is likely that the community organization, which served as a sponsor for this application, contributes directly to community resilience through programs and initiatives that enhance social capital and resource acquisition and mobilization.